Development, transformations and the human condition
1 online resource
Keywords: "The world is grappling to come up with alternative imaginations for transformation despite repeated crises, inequalities and immiseration caused by the increasing dominance of the neo-liberal capitalist framework and the collapse of twentieth-century socialist models. This book looks at concepts that form the core of development economics and political economy and brings together perspectives that explore the inextricable relationship between development and human rights, social movements and the call for social transformation. The essays in this volume honour the massive corpus of work across a large number of areas around development issues by the eminent economist, Jayati Ghosh. The book includes contributions by academics, activists and practitioners and attempts to understand the socio-economic causes of inequality, poverty and oppression. Divided in five sections-corresponding broadly to key areas of Ghosh's work-the book explores capitalism; inequality and development; gender and development; political economy of trade and financial systems; human development and human rights; and music. The volume situates Ghosh's work within a heterodox and broad-based understanding of development processes and provides many insights towards a new vision that sets an agenda for further research as well as mobilisation. This volume will be of great interest to students, researchers, practitioners and scholars working on the issues of development, transformations, political economy, social science, economics, macroeconomics, international economics, politics, and development studies"--